Fungos com potencial toxigênico associados a grãos ardidos de milho - Micheli, Adriana (2016)
The occurrence of rot or stained grains is an important indicator of the quality of maize. Several fungi with toxigenic potential are associated with damaged kernels, however little is known regarding the composition of species and the factors that influence the composition of species in the different regions that produce corn in the country. Such information is important in the study of measures of reduction of rot grains and mycotoxins in maize. This study analyzed the fungal species with toxicogenic potential in samples of rot grains, from different hybrids grown in three locations in Paraná, in two crops. For quantification of genera and species of fungi present in the samples was employed Blotter test with morphological identification of Fusarium, Aspergillus, Penicillium and species Stenocarpella maydis (= Diplodia maydis) and S. macrospora (= D. macrospora). The identification of Fusarium species was performed by PCR with species-specific primers and partial sequencing of TEF-1 gene. Isolates of the species F. verticillioides, Fusarium sp., other species of F. fujikuroi complex and non-identified species were phylogenetically characterized by DNA sequences of the TEF-1 gene (~ 650 pb). The analysis of the incidence of fungi in rot grain samples by Blotter test were subjected to statistical analysis of factorial experiments, in which the factors considered were: crop year (2011/12 and 2012/13), local (Arapoti, Castro and Tibagi) and corn hybrids (eleven commercial hybrids). There was a significant effect (p≤0.05) of the crop, location and genotypes, and the interactions between these factors, on the incidence of all the fungi analized except to S. maydis, for wich the effect of the crop year were not significant. The incidence of fungi in rot grains is not related with the incidence of rot grains in the analized samples. The rates of these fungi ranged from 8.6 to 19.9% for Fusarium spp; 0 to 22.4% for S. macrospora; 0.5 to 2.9% S. maydis; 1.6 to 6.9 for Penicillium spp; and from 0.1 to 2.5% for Aspergillus spp. The molecular identification of Fusarium species was based on spore isolates obtained from analysis of rot grains of two hybrids in the crop 2012/13 and four hybrids in the crop 2014/15 at two sites (Castro and Arapoti), showed that for both crops, the predominant species was F. verticillioides (92.6 and 92.3%) in Arapoti, and (56.7 and 51.6%) in Castro, followed by Fusarium sp. (7.4 to 7.7%) in Arapoti, and (20.0 and 18.8%) in Castro, other species of the F. fujikuroi complex (0.0%) in Arapoti, and (13.3 to 28.1%) in Castro, F. proliferatum (0.0%) in Arapoti and (3.3 and 0.0%) in Castro, Fusarium incarnatum (0.0%) in Arapoti and (0.0 and 1.6%) in Castro. The phylogenetic analysis based on DNA sequences of the TEF-1 gene did not show evidence of structuring of F. verticillioides in subpopulations; while for Fusarium sp.e other species of F. fujikuroi complex was evidence of structure in subpopulations.